The UNHCR and the Management of Liberian Refugees in Nigeria, 1990-2007 - Olusesi Adewunmi OSUNKOYA (International Studies Journal)
The main thrust of this paper is to critically interrogate the management of Liberian refugees in Nigeria between 1990 and 2007. Nigeria was major host country of Liberian refugees in West Africa in particular and Africa in general during this period of study. United Nations High Commissioner for Refugee was the main agency of the United Nations charged with the responsibility of providing humanitarian assistance to refugees. Through effective collaboration with the government of Nigeria, the UNHCR succeeded in managing Liberian refugees in the country. Major steps taken by UNHCR in conjunction with the governmentof Nigeria towards the management of Liberian refugees during this period were the enactment of refugee laws, the establishment of refugee camps and refugee boards and successful implementation of durable solutions to the problem of the refugees. This is a major contribution of this study, which differ from existing studies that focused on the courses and course of the civil war. The methodology adopted in the study was historical, thematic, qualitative and quantitative utilizing both primary and secondary sources of data collection.